Spatiotemporal patterns of phytoplankton communities in coastal waters near the Taishan Nuclear Power Plant - Jingxin Wei; Pei Jiang; Rui He; Zhihao Yang; Qi Chen; Yingshi Ou; Yan Zhang; Bingqing Xiao; Lei Xu; Songhui Lu (Marine Environmental Research, 2026)

Establishment of TaqMan quantitative PCR assays for Karenia species along the Chinese coast - Kemeng Liu; Yu Zhen; Xiaoyu Chi; Songhui Lu; Jingyi Cen; Jian Yuan; Jianyan Wang (Journal of Applied Phycology, 2026)

Insights into variations of environmental factors before and after fish cage removal in Daya Bay, the South China Sea - Hu Zheng; Chaofan Wang; Changliang Xie; Jiazhuo Chen; Songhui Lu; Zhaohui Wang (Journal of Environmental Sciences, 2026)

Operational monitoring windows from cumulative rainfall to chlorophyll-a in subtropical reservoirs - Jingxin Wei; Peiliang Chen; Xingcheng Fu; Jie Ling; Bingqing Xiao; Xuedong Xie; Bozhu Huang; Jingyi Cen; Songhui Lu (Environmental Monitoring and Assessment, 2026)

Beware of phycotoxin (okadaic acid and dinophysistoxin-1) accumulation in early post-restoration period - Qi Qiao; Yuelei Dong; Jian Zou; Tao Zhao; Yuchen Qu; Yuhang Fang; Jingyi Cen; Songhui Lu; Lei Cui (Water Research, 2026)

Tropical coastal seas are overlooked hotspots of Pseudo-nitzschia diversity - Biaobiao Niu; Cuiwen Liang; Fang Yue; Shiyu Wu; Yang Li; Songhui Lu (Harmful Algae, 2026)

Ecotypic differentiation in motility and photoadaptation strategies between epibenthic and benthic Prorocentrum Lima complex - Jie Lin; Hua Zhang; Yiyi Cai; Songhui Lu; Heng Chen (Marine Biology, 2026)

Contradictive effects of light on diarrhetic shellfish toxin production-depending on photosynthetic status and photoprotection ability of Prorocentrum lima strains - Heng Chen; Ruiwang Wei; Zehui Huang; Hua Zhang; Kaixuan Huang; Songhui Lu (Algal Research, 2025)

Multi-omics analysis reveals potential mechanisms of diarrhetic shellfish toxin and fatty acid synthesis in marine harmful Prorocentrum - Danlin Zheng; Ligong Zou; Jian Zou; Qun Li; Songhui Lu (Journal of Hazardous Materials, 2025)

Kareniaceae in focus: A molecular survey of harmful algal dinoflagellates in the South China Sea - Yuping Lv; Yu Zhen; Jingyi Cen; Songhui Lu; Mingmin Li; Yifan Liu; Xiaoyu Chi; Jian Yuan; Jianyan Wang (Harmful Algae, 2025)

Phosphorus rather than nitrogen driving biosynthesis of diarrhetic shellfish toxins in Prorocentrum caipirignum via ATP - Heng Chen; Zehui Huang; Wanchun Guan; Kaixuan Huang; Lei Cui; Hua Zhang; Songhui Lu (Harmful Algae, 2025)

High light and nitrogen deficiency synergistically lead to biofuel and biomass accumulation in diatoms - Lei Cui; Baoling Yang; Liying Tan; Juanchan Xu; Lei Xie; Wenqing Jiang; Mingcan Gu; Xiang Wang; Songhui Lu; Jianwei Zheng; Yuelei Dong (Chemical Engineering Journal, 2024)

Five Karenia species along the Chinese coast: With the description of a new species, Karenia hui sp. nov. (Kareniaceae, Dinophyta) - Jingyi Cen; Songhui Lu; Øjvind Moestrup; Tao Jiang; Kin Chung Ho; Si Li; Mingmin Li; Qingliu Huan; Jianyan Wang (Harmful Algae, 2024)

Prediction of Aureococcus anophageffens using machine learning and deep learning - Jie Niu; Yanqun Lu; Mengyu Xie; Linjian Ou; Lei Cui; Han Qiu; Songhui Lu (Marine Pollution Bulletin, 2024)

Adaptive responses of geographically distinct strains of the benthic dinoflagellate, Prorocentrum lima (Dinophyceae), to varying light intensity and photoperiod - Haiyan Wu; Haoyu Zhang; Jixing Peng; Guanchao Zheng; Songhui Lu; Zhijun Tan (Harmful Algae, 2023)

Sublethal effects on the hard clam Mercenaria mercenaria after exposure to Aureococcus anophagefferens Chinese strain isolates - Yuelei Dong; Jian Gao; Jingyi Cen; Jing Zhang; Songhui Lu; Lei Cui (Harmful Algae, 2023)

Diarrhetic shellfish toxins production appears to be driven by photosynthesis and phosphate–revealed by different light-adapted strains of Prorocentrum lima complex and P. caipirignum - Heng Chen; Kaixuan Huang; Wanchun Guan; Hua Zhang; Shasha Liu; Songhui Lu (Frontiers in Marine Science, 2023)
Introduction Diarrhetic shellfish toxins (DST) harm shellfish aquaculture and endanger human health, and include well-known marine dinoflagellate-produced toxins such as okadaic acid (OA) and analogues, such as dinophysistoxin-1 (DTX-1). Toxin-producing species have different toxin profiles and contents, with unclear interactions, with the toxins hypothesized to be produced under stress conditions. Methods Five morphotypes of Prorocentrum lima complex, a well-studied DST-producing species with remarkable phylogenetic variability, were chosen and exposed to three distinct light conditions (photosynthetic active radiation, PAR; PAR+UVA; PAR+UVA and UVB) for 18 or 24 days. Results and discussion The studied morphotypes were classified as either light-sensitive (LS) or light-tolerant (LT) types based on their light responses and varying abilities to produce DTX-1 across three orders of magnitude (0.001-1 pg cell -1 d -1 , abbreviated as LL, ML, and HL in order of rank). All toxin production rates ( R tox ) initially increased and then decreased, with the first peaks varying between days 3 to 12. The results of earlier peaks in LL and ML and a linear correlation between R tox values for OA and DTX-1 in HL indicated that the two compounds may be competitive. When light conditions initially altered, R tox was either stagnant or negative under all light treatments in the LS cohort, and with UV addition in LT, which subsequently delayed the early peaks. The R tox data for DTX-1 all demonstrated earlier and higher peaks with UVA addition in LL and ML. Likewise, their growth was facilitated following the addition of UVA light. Therefore, R tox of pre-peaks is relevant to photosynthetic status and photoprotection ability. As decreasing R tox data points corresponded closely with phosphate depletion, the phosphate consumption rate was calculated and shown to be linearly or exponentially associated with all downward R tox . This study proposes a supply-demand link between photosynthetic products and phosphate with DST biosynthesis, inferring a likely competitive interaction between OA and DTX-1 production.

Light-induced algae retinal stress can deform fish spines - Yuelei Dong; Xiaoyu Zhou; Jianwei Zheng; Jingyi Cen; Yuzao Qi; Songhui Lu; Lei Cui (Aquaculture, 2023)

Allelopathic Interactions Between the Tropical Macrophyte Enhalus acoroides and Epibenthic HAB Dinoflagellate Prorocentrum concavum - Hui Liu; Jian Zou; Hang Xie; Chengzhi Zheng; Songhui Lu (Journal of Ocean University of China, 2022)

Spatial-Temporal Distribution of Prorocentrum concavum Population in Relation to Environmental Factors in Xincun Bay, a Tropical Coastal Lagoon in China - Jian Zou; Hang Xie; Chengzhi Zheng; Songhui Lu (Frontiers in Marine Science, 2022)
A harmful benthic Prorocentrum concavum bloom was recorded in August 2018 in Xincun Bay, China, which is the location of a national seagrass nature reserve. Annual ecological surveys have been conducted to study the population dynamics of P. concavum in the benthic community and water column. Seasonal variations in benthic P. concavum abundance were found and the abundances on seagrass and macroalgae in the wet season were 2.5 and 2.82 times higher, respectively, than those in the dry season, although the differences were not statistically significant. The abundance of P. concavum in the water column differed significantly between seasons. The maximum abundances of benthic and planktonic P. concavum were (1.7 ± 0.59) × 106 cells (100 cm2)−1 on Thalassia hemperichii in July and 2.0 × 104 ± 4.7 × 103 cells L−1 in June, respectively. High spatial heterogeneity in P. concavum abundance was observed among five sampling sites. Abundances were significantly higher in seagrass beds than those in macroalgae beds, mangroves, and coral reefs. The abundance of P. concavum at site A (in a seagrass bed and close to a cage-culture area) was 5.6 times higher than that at site D (seagrass bed and distant from the cage-culture area). Planktonic P. concavum showed a similar spatial distribution and presented a maximum density at site A. Moreover, the abundance of benthic P. concavum also showed heterogeneity on host substrates, and the abundance on T. hemperichii was significantly higher than that on sediment. Based on a Spearman’s test, temperature, dissolved organic phosphorus, and dissolved organic nitrogen were the three important factors driving the spatiotemporal distribution of benthic P. concavum in Xincun Bay. Planktonic P. concavum were derived from cells on the substrates and were influenced by concentrations of dissolved oxygen. In conclusion, seagrass beds may be a reservoir of harmful benthic algal blooms in Xincun Bay and the dense cage-culture area provides sufficient organic nutrients for the growth and reproduction of benthic dinoflagellates.

Dissolved Organic Matter and Activities of Extracellular Enzymes in Two Lagoons (South China Sea) Affected by Aquaculture - Linjian Ou; Jianting Li; Xianyang Zhang; Zhou Wang; Jian Zou; Songhui Lu (Frontiers in Marine Science, 2022)
Xincun Lagoon and Li’an Lagoon are typical tropical lagoons containing unique seagrass meadow and mangrove forest ecosystems. However, nutrient pollution from human activities threatens ecosystem health in these areas. A year-long bimonthly survey was carried out to study the bioavailability of organic nutrients through hydrolysis of the extracellular enzymes β-glucosidase (GLU), leucine aminopeptidase (LAP), and alkaline phosphatase (AP) in the two lagoons. The results showed that the nutrient statuses in Xincun Lagoon and Li’an Lagoon were highly variable and enriched with organic nutrients, especially nitrogen. Organic nitrogen and phosphorus were actively recycled in the lagoons through active LAP and AP hydrolysis. The enzyme activities were mostly produced by particulate-associated bacteria and were positively regulated by the existence of organic nutrients. The enzymatic stoichiometry results indicated the importance of dissolved proteins and aminopolysaccharides as sources of both carbon and nitrogen and a potential phosphorus limitation on microbial growth in the lagoons. Our results emphasized the importance of EEAs in the recycling of organic nutrients and the potential influence of enriched organic nutrients on both microorganisms and plants in Xincun Lagoon and Li’an Lagoon.

Effects of temperature on the growth and carbohydrate production of three benthic dinoflagellate species from Hainan Island, South China Sea - Zhen Wu; Hua Zhang; Qun Li; Lei Cui; Heng Chen; Songhui Lu (Ecotoxicology, 2021)

Effects of Ultraviolet (UV) Radiation on Outdoor- and Indoor-Cultured Prorocentrum lima, a Toxic Benthic Dinoflagellate - Heng Chen; Kaixuan Huang; Shasha Liu; Songhui Lu (Journal of Ocean University of China, 2021)

Characterization of the Complete Mitochondrial Genome of Arius dispar (Siluriformes: Ariidae) and Phylogenetic Analysis Among Sea Catfishes - Lei Cui; Yuelei Dong; Rongbo Cao; Xiaoyu Zhou; Songhui Lu (Journal of Ocean University of China, 2020)

Diversity and geographical distribution of resting stages of eukaryotic algae in the surface sediments from the southern Chinese coastline based on metabarcoding partial 18S rDNA sequences - Lei Liu; Zhaohui Wang; Songhui Lu (Marine Ecology, 2020)
Surface sediment samples were collected from sixteen sites of the southern Chinese coastline in this study. Diversity of eukaryotic microalgae was examined using high‐throughput sequencing of 18S rDNA to understand the community structure and geological distribution of microalgal resting stages. A total of 218 operational taxonomic units (OTUs) were detected for eukaryotic algae, and only 75 OTUs (34.40%) were detected into species level. The algal communities were composed of sixty‐four genera belonged to twelve classes of four phyla. Dinoflagellates were the most abundant and diversified group, which accounted for the average of 56.26% and 53.70% DNA reads and OTUs, respectively. Dinoflagellates were dominated by Protoperidinium , Euduboscquella , Amylax , and Paragymnodinium . Chaetoceros, Thalassiosira , and Skeletonema were abundant in diatoms, while Pedospumella and Paraphysomonas in Chrysophyceae were the most abundant genera due to their massive occurrence in some particular sites. The high abundance of Protoperidinium sequences suggested the high nutrient levels in the southern Chinese coastline. Nineteen of the detected OTUs were assigned to harmful and/or bloom‐forming microalgae. The wide occurrence of the toxic dinoflagellate Azadinium poporum and high abundance of Alexandrium pacificum in some particular sites suggested the potential risk of human poisoning.

Probabilistic health risk assessment of nitrosamines in drinking water of Shaoxing, Zhejiang, China - Yuanyuan Yin; Tong Li; Duyi Kuang; Yuanan Lu; Yan Shen; Jun Xu; Songhui Jiang; Xia Wang (Environmental Science and Pollution Research, 2019)

Response of size-fractionated phytoplankton to environmental factors near the Changjiang Estuary - Li Li; Jingyi Cen; Lei Cui; Songhui Lu (Acta Oceanologica Sinica, 2019)

Grazing and performance of the copepod Pseudodiaptomus poplesia on a Chinese strain of Aureococcus anophagefferens - Xuejia He; Didi Han; Liuyu Han; Songhui Lu (Acta Oceanologica Sinica, 2018)

Temporal and spatial variations of abundance of phycocyanin- and phycoerythrin-rich Synechococcus in Pearl River Estuary and adjacent coastal area - Tao Jiang; Chao Chai; Jifang Wang; Ling Zhang; Jingyi Cen; Songhui Lu (Journal of Ocean University of China, 2016)

Growth and competition for different forms of organic phosphorus by the dinoflagellate Prorocentrum donghaiense with the dinoflagellate Alexandrium catenella and the diatom Skeletonema costatum s.l. - Linjian Ou; Xiaoyun Huang; Bangqin Huang; Yuzao Qi; Songhui Lu (Hydrobiologia, 2015)

Effects of temperature and organic and inorganic nutrients on the growth of Chattonella marina (Raphidophyceae) from the Daya Bay, South China Sea - Zhaohui Wang; Meiling Yuan; Yu Liang; Songhui Lu (Acta Oceanologica Sinica, 2011)

Harmful algal bloom causative collected from Hong Kong waters - Songhui Lu; I.J. Hodgkiss (Hydrobiologia, 2004)

The effects of nutrients and their ratios on phytoplankton abundance in Junk Bay, Hong Kong - I.J. Hodgkiss; Songhui Lu (Hydrobiologia, 2004)

Some observations on harmful algal bloom (HAB) events along the coast of Guangdong, southern China in 1998 - Yuzao Qi; Jufang Chen; Zhaohui Wang; Ning Xu; Yan Wang; Pingping Shen; Songhui Lu; I.J. Hodgkiss (Hydrobiologia, 2004)